Production and kinetic study of torrefied oil palm frond and Leucaena Leucocephala pellets for co-combustion with silantek coal / Sharmeela Matali - Matali, Sharmeela (2019)
Biomass in Malaysia has potential to be converted into high quality solid biofuels by enhancing properties of raw biomass via combined process of densification and torrefaction. Torrefaction, also known as mild pyrolysis, is generally carried out between temperature range of 200 and 300 °C in anoxic conditions, where it has favourable effects on biomass, which includes increasing its energy density and eliminating problems commonly associated with raw biomass such as high moisture content, hygroscopic behaviour and low calorific value. In this study, torrefaction of agricultural plantation residue, oil palm frond (OPF, non-woody biomass) and short rotation energy crop, Leucaena Leucocephala (LL, woody biomass) were conducted in a horizontal tube furnace at five temperatures and holding time of 15–60 min. These torrefied biomass pellets can be used as a highly viable feedstock in thermochemical processes such as gasification and as a substitute to coal in thermal power plants and metallurgical processes. Torrefaction is influenced by many factors where among the strong factors are biomass lignocellulosic composition, temperature and residence/holding time. Results obtained in this study showed high energy densification factor of produced biomass pellets in the maximum range of 1.46–1.50, calorific value increment of 50–54%, and improved hydrophobicity at 23–35%. Via FTIR, the most significant structural changes brought by torrefaction were on the hydroxyl stretch (–OH) and C–O stretch due to the reductions of hydrogen and oxygen atoms in the biomass structure where consequently, lignin-related concentrated bonds are high and atomic ratios O/C and H/C reduced significantly causing favourable fuel ratio to increase up to 1.06. In order to obtain sufficiently high mass-energy properties, optimisations via response surface methodology (RSM) incorporating central composite design (CCD) were carried out. Results showed temperature is the most influential factor during torrefaction process while holding time effect was absent for oil palm frond and very minimal for Leucaena Leucocephala. Torrefaction and co-combustion kinetic studies were performed via non-isothermal thermogravimetric analysis. The most reliable method was identified to be Coat-Redfern method with high correlation coefficients (R2 ≥ 0.965) for both processes. Via this method, reaction mechanisms during torrefaction were identified to be reaction order and diffusion for OPF and LL, respectively. As for co-combustion kinetic study, both torrefied biomass and Silantek coal followed diffusion reaction mechanism. Co-combustion of coal and torrefied biomass was dominated by char combustion stage, in which activation energies of the blends decreased up to 43% where the lowest Ea was obtained at 40% TOPFP (77.33 kJ/mol) and at 50% TLLP (65.30 kJ/mol). The information regarding biomass torrefaction and combustion/co-combustion kinetics is needed to accurately predict reactions behaviour, as well as to optimise and control the process of conversion toward products during the thermal degradation.